Pendampingan diversifikasi produk Tanaman Obat Keluarga (TOGA) berbasis kunyit sebagai upaya penguatan keterampilan Kelompok MPS Botani di SMAN 1 Bangkalan - Devi Anggraini Putri; Rizka Efi Mawli; Nurina Rizka Ramadhania; Metta Kristina (Penamas: Journal of Community Service, 2026)
The diversification of family medicinal plant products (TOGA) is an important strategy to support the Sustainable Development Goals (SDGs) by producing health-related products that can improve public health. In the previous community service program, the team succeeded in increasing health independence among the younger generation through training in the diversification of traditional medicine products. This program aims to improve the sustainability of toga-processed traditional medicine and to analyse the macronutrient content (proximate analysis) and hedonic properties of diversified traditional medicine products. The implementation method is divided into three steps: implementation, monitoring, and evaluation. The implementation of the activity yielded three diversified traditional medicine products made from turmeric: turmeric tamarind spice drink, instant turmeric creamer powder, and instant turmeric spice powder. Based on the proximate test results, all three products contain carbohydrates, protein, and fat. The hedonic test results showed that the instant turmeric powder with creamer was the most popular, with an average score of 4.26 across taste, aroma, colour, texture, sensation, aftertaste, and flavour strength. The mentoring activities to diversify turmeric-based herbal products are recommended for the younger generation.